Rekonstruksi Teori Hukum Informasi dalam Menghadapi Berita Palsu: Analisis Etika Media Digital Berbasis Regulasi dan Maqāṣid al-Sharīʿah - Mochamad Riyanto; Ahmad Roihan Firdiansyah (Universitas Islam Negeri Antasari Banjarmasin, 2025)
The spread of fake news in the digital era has posed complex challenges to journalism ethics, legal regulation, and social stability. Existing information laws tend to be reactive and have not integrated ethical dimensions or religious values. This study presents a new theoretical model based on maqāṣid al-sharīʿah, integrating professional ethics, positive law, and Islamic legal principles as a framework for reconstructing Media and Press Law. Using a normative-qualitative approach, this study analyzes press regulations in Indonesia, selected scientific literature, and Islamic legal doctrine—particularly the concepts of taʿzīr and maqāṣid al-sharīʿah—through thematic analysis with source selection criteria and a conceptual coding process to identify gaps between media ethics, regulations, and fiqh. This approach examines how misinformation and disinformation threaten the protection of reason (ḥifẓ al-ʿaql) and religion (ḥifẓ al-dīn), which are the core objectives of Sharia. The study's results indicate that integrating the principles of information verification (tabayyun), accountability, and public responsibility into the legal system and journalistic practices can increase resilience to disinformation. The information governance model based on maqāṣid, formulated in this study, is a conceptual contribution that aligns law enforcement with journalistic ethics, ensuring that freedom of expression remains guaranteed while upholding the collective obligation to maintain truth and justice in the digital public space. In addition, this study proposes policy indicators that translate the objectives of maqāṣid al-sharīʿah into regulatory measures that can be implemented by media institutions and state authorities, thereby building an adaptive and ethically based regulatory framework to address the threat of disinformation within the scope of Media and Press Law.